Delivering the people's message : the changing politics of the presidential mandate - Azari, Julia R., 1979- (Cornell University Press, 2014)
Presidents have long invoked electoral mandates to justify the use of executive power. In Delivering the People's Message, Julia R. Azari draws on an original dataset of more than 1,500 presidential communications, as well as primary documents from six presidential libraries, to systematically examine choices made by presidents ranging from Herbert Hoover in 1928 to Barack Obama during his 2008 election. Azari argues that Ronald Reagan's election in 1980 marked a shift from the modern presidency formed by Franklin Delano Roosevelt to what she identifies as a more partisan era for the presidency. This partisan model is a form of governance in which the president appears to require a popular mandate in order to manage unruly and deeply contrary elements within his own party and succeed in the face of staunch resistance from the opposition party. Azari finds that when the presidency enjoys high public esteem and party polarization is low, mandate rhetoric is less frequent and employs broad themes. By contrast, presidents turn to mandate rhetoric when the office loses legitimacy, as in the wake of Watergate and Vietnam and during periods of intense polarization. In the twenty-first century, these two factors have converged. As a result, presidents rely on mandate rhetoric to defend their choices to supporters and critics alike, simultaneously creating unrealistic expectations about the electoral promises they will be able to fulfill.